Functional Analysis of a Novel Complement C5a Receptor 1-Blocking Monoclonal Antibody - Leon Cyranka; Ida Mariegaard; Mikkel-Ole Skjødt; Rafael Bayarri-Olmos; Tom Eirik Mollnes; Peter Garred; Anne Rosbjerg (Karger Publishers, 2023)
Introduction: The complement system anaphylatoxin C5a is a critical player in inflammation. By binding to complement C5a receptor 1 (C5aR1/CD88), C5a regulates many cellular functions, mainly as a potent pro-inflammatory inducer. We describe the generation and selection of a potent antagonistic C5aR1 mouse monoclonal antibody (mAb). Methods: Initial C5aR1 hybridoma clone selection was performed with a cell-binding study in human whole blood. In-house C5aR1 mAb assessment for C5aR1 inhibition was done via the iLite® C5a assay. C5aR1 mAb specificity was investigated on C5aR1his- and C5aR2his-expressing Flp-In™-CHO cells. Physiological C5aR1 inhibition was assessed via a C5a-driven calcium flux assay and stimulation assay based on isolated polymorphonuclear leukocytes (PMNs) and a whole blood model stimulated with Escherichia coli. Results: The supernatant of hybridoma clones targeting the N-terminal section of C5aR1 displayed efficient binding to C5aR1 in whole blood, which was confirmed for purified mAbs. The C5aR1 mAb 18-41-6 was selected following the assay of in-house C5aR1 mAbs via the iLite® C5a assay. The mAb 18-41-6 was specific for C5aR1. Full-size and/or F(ab')2 preparations of mAb 18-41-6 were found to efficiently abrogate C5a-induced calcium flux in neutrophils and to significantly reduce the upregulation of the activation markers CD11b (neutrophils, monocytes) and CD66b (neutrophils). Conclusion: Our results demonstrate that mAb 18-41-6 is a valuable tool for investigating the C5a-C5aR1 axis and a potential therapeutic candidate for inflammatory disease treatment.